2005
DOI: 10.1111/j.1469-8137.2005.01343.x
|View full text |Cite
|
Sign up to set email alerts
|

Plant–microbe interactions: identification of epiphytic bacteria and their ability to alter leaf surface permeability

Abstract: Summary• Bacteria were either isolated from leaf surfaces of Hedera helix or obtained from a culture collection in order to analyse their effect on barrier properties of isolated Hedera and Prunus laurocerasus cuticles.• On the basis of the 16S rDNA sequences the genera of the six bacterial isolates from Hedera were identified as Pseudomonas sp., Stenotrophomonas sp. and Achromobacter . Water permeability of cuticles isolated from H. helix was measured before and after inoculation with the six bacterial strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 32 publications
(39 reference statements)
3
74
0
4
Order By: Relevance
“…This raises the question as to how the T3SS functions across the plant cuticle. Several different bacterial epiphytes can alter leaf surface properties and affect cuticle permeability (Schreiber et al, 2005). We hypothesize that Psy728a can also modify cuticle properties to allow access of the T3SS secretion needle to the plant epidermal cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…This raises the question as to how the T3SS functions across the plant cuticle. Several different bacterial epiphytes can alter leaf surface properties and affect cuticle permeability (Schreiber et al, 2005). We hypothesize that Psy728a can also modify cuticle properties to allow access of the T3SS secretion needle to the plant epidermal cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, living conditions in the habitat phyllosphere are improved. It can be concluded that the ability to change leaf surface properties will improve epiphytic fitness of pseudomonads (Schreiber et al, 2005). Legard et al (1994) reported 15 bacteria were frequently recovered and identified on wheat leaves in the glasshouse and field, but only Pseudomonas aureofaciens kept similar frequency in all experiments.…”
Section: Dgge and Diversity Analysismentioning
confidence: 96%
“…(WD4, WD14 and WD16) were the favorite bacteria and grew well on the control wheat leaves according DGGE through this experiment, which was similar to the clone library analysis. Schreiber et al (2005) reported that the inoculation of Pseudomonas sp. increased water permeability of Hedera and Prunus cuticles, which in turn increase the availability of water and dissolved compounds in the phyllopshere.…”
Section: Dgge and Diversity Analysismentioning
confidence: 99%
“…A smooth cuticle was reported in Mikania lanuginosa leaves [37], whereas varied cuticular ornamentation (smooth, undulating, wrinkled, or striated) was observed in several species of the genus Cyanus [38]. As a chemically stable epidermal layer, the cuticle serves a very important function in plant water metabolism and constitutes a mechanical protective barrier against abiotic environmental factors, pathogenic microbial penetration, and pest infestation inside the organ [39][40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%